2020
DOI: 10.1029/2019wr026130
|View full text |Cite
|
Sign up to set email alerts
|

A Tree‐Based Direct Sampling Method for Stochastic Surface and Subsurface Hydrological Modeling

Abstract: Direct sampling (DS) is a versatile multiple‐point statistics method for generating spatial‐temporal geostatistical models. DS is known for being able to address a variety of training images and hence spatiotemporal stochastic modeling problems. One limitation of DS is the central processing unit (CPU) time, mostly attributed to the use of a random search for patterns in the training image. To improve CPU performance, we propose a tree‐based direct sampling (TDS) method. In our method, training patterns are gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 63 publications
0
14
0
Order By: Relevance
“…Stochastic modeling is thus a promising tool for ice-sheet investigations, which has prompted several previous studies on subglacial topographic simulation methods and applications (Goff and others, 2014; Graham and others, 2017; MacKie and others, 2020; Zuo and others, 2020). MacKie and others (2020) generated multiple topographic realizations and used these to investigate uncertainty in the surface area and locations of subglacial lakes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stochastic modeling is thus a promising tool for ice-sheet investigations, which has prompted several previous studies on subglacial topographic simulation methods and applications (Goff and others, 2014; Graham and others, 2017; MacKie and others, 2020; Zuo and others, 2020). MacKie and others (2020) generated multiple topographic realizations and used these to investigate uncertainty in the surface area and locations of subglacial lakes.…”
Section: Introductionmentioning
confidence: 99%
“…MacKie and others (2020) generated multiple topographic realizations and used these to investigate uncertainty in the surface area and locations of subglacial lakes. Zuo and others (2020) simulated long-wavelength (>10 km) topography and found that, on average, the water flowpath locations in simulated topography differed significantly from those with kriged topography. However, evaluating the sensitivity of water routing to small-scale roughness requires further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Originally, Goodfellow, Pouget-Abadie [9] proposed the loss function given below in (2), where the last layer of is a sigmoid function.…”
Section: Gan Lossmentioning
confidence: 99%
“…These traditional methods have various advantages and disadvantages. Some of them are still under research, such as the development of tree-based direct sampling MPS method [2] and many variations of forward stratigraphic modelling (e.g. [3]).…”
Section: Introductionmentioning
confidence: 99%
“…These approaches have various advantages and disadvantages, and they have been widely used in different scenarios. Some of them are still under research, such as the recent development of the tree-based direct sampling MPS method (Zuo et al 2020).…”
Section: Introductionmentioning
confidence: 99%